EVALUASI DESKRIPTIF POSTUR KERJA DENGAN METODE REBA UNTUK MSDS : STUDI KASUS PADA PEKERJA LOADER LOGISTIK KOTA MAKASSAR : DESCRIPTIVE EVALUATION OF WORK POSTURE USING THE REBA METHOD FOR MSDS: A CASE STUDY OF LOGISTIC LOADER IN MAKASSAR - Rahmadani, Yulianah; Syafitri, Nurul Mawaddah; Hamid, Fatmawati (Politeknik Insan Husada Surakarta, 2026)
Background: Informal sector workers in Makassar City are vulnerable to musculoskeletal disorders (MSDs) due to working conditions with minimal ergonomic standards. Work posture evaluation is needed to map the level of risk and design appropriate interventions.Purpose: To evaluate the level of risk of work posture among informal workers in Makassar City using the Rapid Entire Body Assessment (REBA) method to describe the potential for MSDs.Methods: A descriptive observational study with a cross-sectional approach was conducted on 30 active informal workers in Makassar who performed manual work with a dominant posture of standing, bending, or lifting their hands. Data collection was conducted in December 2025 using the REBA observation sheet to assess work posture holistically.Result: The REBA score showed an average of 7.8 (median 8). Forty percent of workers (n=12) were in the moderate risk category (score 4-7), 46.7% (n=14) were in the high risk category (score 8-10), and 13.3% (n=4) were in the very high risk category (score ?11). The majority of workers (86.7%) required ergonomic improvements, ranging from those that needed to be done immediately to those that were very urgent.Conclusion: The working posture of informal workers in Makassar is generally classified as moderate to high ergonomic risk, indicating a significant potential for MSDs. Simple and contextual ergonomic interventions, such as improving work positions, adjusting tools, and providing education, are needed to reduce risks and improve occupational safety and health.